2010
DOI: 10.1292/jvms.09-0480
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Secretion and Ovarian Function in Cycling and Non-Cycling African Female Elephants (Loxodonta africana)

Abstract: ABSTRACT. Reproduction of captive elephants in zoos has shown a low fecundity and requires improvement. One of the reasons for low fecundity is ovarian dysfunction in many female elephants. To investigate whether prolactin has a correlation with ovarian function in female elephants, the serum concentrations of prolactin, progesterone and estradiol-17 in four African female elephants (one cycling female and three non-cycling female elephants) were measured. Cyclic patterns of prolactin and estradiol-17 were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Prolactin: Concentrations of PRL in elephant sera and placentae were determined by a heterologous RIA system using an antihuman PRL rabbit sera (NIDDK-anti-hPRL-3, National Institute of Diabetes and Digestive and Kidney Diseases, Torrance, CA, USA), iodinated ovine PRL (NIDDK-oPRL-I-2), ovine PRL standard (NIDDK-RP-2) and goat anti-rabbit gamma globulin (ARGG) as previous described [22]. Thus, PRL levels are referred to as immunoreactive (ir-) PRL in the present paper.…”
Section: Radioimmunoassays (Ria)mentioning
confidence: 99%
See 2 more Smart Citations
“…Prolactin: Concentrations of PRL in elephant sera and placentae were determined by a heterologous RIA system using an antihuman PRL rabbit sera (NIDDK-anti-hPRL-3, National Institute of Diabetes and Digestive and Kidney Diseases, Torrance, CA, USA), iodinated ovine PRL (NIDDK-oPRL-I-2), ovine PRL standard (NIDDK-RP-2) and goat anti-rabbit gamma globulin (ARGG) as previous described [22]. Thus, PRL levels are referred to as immunoreactive (ir-) PRL in the present paper.…”
Section: Radioimmunoassays (Ria)mentioning
confidence: 99%
“…The major source of PRL is the anterior pituitary gland, and its major functions during mammalian gestation are development of the mammary glands and stimulation of milk production. PRL secretion is stimulated by several environmental factors including pregnancy, suckling stimulation and stress [2,[6][7][8][9][10][11][12].Reproductive endocrinology including secretion of PRL has been studied in elephants previously [13][14][15][16][17][18][19][20][21][22]. However, many mysteries, such as the source and the function of PRL during pregnancy, still remain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors found acyclicity to be related to hyperprolactinemia (Yamamoto et al. , Brown et al. ) and levels of prolactin were found to be positively correlated with cortisol levels in captive African elephants (Bechert et al.…”
Section: Factors Influencing Reproduction In Free‐ranging Semi‐captimentioning
confidence: 99%
“…While the majority of publications on zoo elephants focus on acyclicity and potential causes (Yamamoto et al. , Glaeser et al. , Brown et al.…”
Section: Introductionmentioning
confidence: 99%